Characteristics of Career Planners in Upwardly Mobile Occupations. - Gould, S. (Academy of Management Journal, 1979)
Career variables of 277 municipal employees of a large southwestern city in upwardly mobile occupations were surveyed with a questionnaire instrument. Analysis of the collected data revealed that i...